Glass cloth treatment liquid and surface-treated glass cloth
By using an organic silicon compound treatment solution containing (meth)acrylic acid group and an aliphatic unsaturated hydrocarbon group, the problem of insufficient adhesion between the glass cloth and the resin is solved, and the reliability and heat resistance of the printed circuit board are improved.
Patent Information
- Application Number
- JP2023120818
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
The existing glass cloth surface treatment agent has insufficient adhesion in high-density and ultra-thin printed circuit boards, resulting in the problem of interface peeling between the glass cloth and the resin. The traditional silane coupling agent performs poorly in terms of heat resistance and alkali resistance, which affects reliability.
The glass cloth is treated with a specific concentration of aqueous solution using an organic silicon compound containing a (meth)acrylic acid group and an aliphatic unsaturated hydrocarbon group as the glass cloth treatment solution to form a high-reliability laminate.
The adhesion between the glass cloth and the resin is improved, the reliability and heat resistance of the printed circuit board are enhanced, and the stability during the processing is improved.
Smart Images

Figure 2025017665000001 
Figure 2025017665000002 
Figure 2025017665000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass cloth treatment liquid and a surface-treated glass cloth, and more specifically to a glass cloth treatment liquid containing a (meth)acrylic group-containing organosilicon compound and a carbon-carbon double bond-containing organosilicon compound, and a surface-treated glass cloth that has been surface-treated with the treatment liquid. [Background technology]
[0002] Currently, with the increasing performance and high-speed communication of information terminals such as smartphones, the printed wiring boards used are becoming increasingly dense and extremely thin, as well as lowering the dielectric constant and dielectric loss tangent. As an insulating material for these printed wiring boards, laminates are widely used, which are made by laminating prepregs obtained by impregnating glass cloth with thermosetting resins such as epoxy resins (hereinafter referred to as "matrix resins") and curing them under heat and pressure. For laminates, the adhesion between the glass cloth and the resin is important, and if the adhesion is insufficient, peeling will occur at the interface between the glass cloth and the resin during the processing of the laminate or after it is manufactured into a product. Generally, glass cloth is treated with a silane coupling agent, and the organic functional groups of the silane coupling agent react with the organic functional groups of the matrix resin to ensure adhesion between the glass cloth and the resin. However, conventional silane coupling agents do not have sufficient adhesion, and there is a demand for silane coupling agents that have higher adhesion, and that can ensure sufficient stability in processing processes such as etching and long-term reliability.
[0003] A representative silane coupling agent used in glass cloth treatment solutions is 3-methacryloxypropyltrimethoxysilane as reported in Patent Document 1. However, laminates using glass cloth whose surface has been treated with 3-methacryloxypropyltrimethoxysilane have poor solder heat resistance and alkali resistance, and have issues with reliability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 194772 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above problems, and has as its object to provide a glass cloth treatment liquid containing a (meth)acrylic group-containing organosilicon compound and an aliphatic unsaturated hydrocarbon group-containing organosilicon compound, glass cloth surface-treated with said glass cloth treatment liquid, and a prepreg and printed wiring board having excellent reliability. [Means for solving the problem]
[0006] As a result of intensive research to solve the above problems, the present inventors have found that a solution in which a specific (meth)acrylic group-containing organosilicon compound and a specific aliphatic unsaturated hydrocarbon group-containing organosilicon compound are dissolved at a specific concentration in a solvent containing water provides a surface-treated glass cloth capable of forming a highly reliable laminate, and have completed the present invention. Note that in the present invention, the (meth)acrylic group means a methacryl group or an acrylic group.
[0007] That is, the present invention provides 1. A glass cloth treatment liquid in which (A) an organosilicon compound represented by the following formula (1) and (B) an organosilicon compound represented by the following formula (2) are dissolved in a solvent containing water, A glass cloth treatment liquid having a concentration of component (A) of 0.05 to 2.0 mass % and a concentration of component (B) of 0.05 to 2.0 mass %. [ka] (In the formula, R 1 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2represents a hydrogen atom or a methyl group, Me represents a methyl group, X represents an oxygen atom or NH, R 3 represents a monovalent aliphatic unsaturated hydrocarbon group having 4 to 12 carbon atoms, m1 and m2 each independently represent an integer of 1 to 3, and n1 represents an integer of 1 to 12. 2. In the above formula (1), R 2 2. The glass cloth treatment solution according to 1, wherein n is a methyl group and n1 is 3. 3. In the above formula (2), R 3 3. The glass cloth treatment solution according to 1 or 2, wherein 4. The glass cloth treatment liquid according to any one of 1 to 3, wherein the water is adjusted to be acidic. 5. A surface-treated glass cloth, the surface of which has been treated with the glass cloth treatment solution according to 4. 6. A prepreg comprising the surface-treated glass cloth according to 5 and a matrix resin impregnated into the surface-treated glass cloth. 7. Printed wiring board using the prepreg described in 6. to provide. Effect of the Invention
[0008] The glass cloth treatment liquid of the present invention provides a surface-treated glass cloth that can be suitably used for printed wiring boards and the like, and can improve the productivity during the production of boards and the reliability of the boards. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. [Glass cloth treatment liquid] The glass cloth treatment liquid of the present invention (hereinafter sometimes referred to as the "treatment liquid") is a glass cloth treatment liquid in which (A) an organosilicon compound represented by the following formula (1) (hereinafter referred to as component (A)) and (B) an organosilicon compound represented by the following formula (2) (hereinafter referred to as component (B)) are dissolved in a solvent containing water.
[0010] [ka]
[0011] In formula (1), R 1 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms; R 2 represents a hydrogen atom or a methyl group, Me represents a methyl group, X represents an oxygen atom or NH, R 3 represents a monovalent aliphatic unsaturated hydrocarbon group having 4 to 12 carbon atoms; each m1 independently represents an integer of 1 to 3; and n1 represents an integer of 1 to 12.
[0012] R 1 The alkyl group having 1 to 10 carbon atoms may be linear, branched, or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups. Among these, R 1 As the alkyl group, an alkyl group having 1 to 3 carbon atoms is preferable, a methyl group or an ethyl group is more preferable, and a methyl group is even more preferable.
[0013] R 2 is a hydrogen atom or a methyl group, and is more preferably a methyl group.
[0014] X is an oxygen atom or NH, and an oxygen atom is more preferred.
[0015] m1 represents an integer of 1 to 3, preferably 2 or 3, and n1 represents an integer of 1 to 3, more preferably 3 from the viewpoint of raw material procurement.
[0016] Specific examples of component (A) include: 3-acryloxypropyltrimethoxysilane, 3-acryloxypropylmethyldimethoxysilane, 3-acryloxypropyldimethylmethoxysilane, 3-acryloxypropyltriethoxysilane, 3-acryloxypropylmethyldiethoxysilane, 3-acryloxypropyldimethylethoxysilane, 3-acryloxymethyltrimethoxysilane, 3-acryloxymethylmethyldimethoxysilane, 3-acryloxymethyldimethylmethoxysilane, 3-acryloxymethyltriethoxysilane, 3-acryloxymethylmethyldiethoxysilane, 3-acryloxymethyldimethylethoxysilane, 3-Methacryloxypropyltrimethoxysilane, 3-Methacryloxypropylmethyldimethoxysilane, 3-Methacryloxypropyldimethylmethoxysilane, 3-Methacryloxypropyltriethoxysilane, 3-Methacryloxypropylmethyldiethoxysilane, 3-Methacryloxypropyldimethylethoxysilane, 3-Methacryloxymethyltrimethoxysilane, 3-Methacryloxymethylmethyldimethoxysilane, 3-Methacryloxymethyldimethylmethoxysilane, 3-Methacryloxymethyltriethoxysilane, 3-Methacryloxymethylmethyldiethoxysilane, 3-Methacryloxymethyldimethylethoxysilane, 3-methacrylamidopropyltrimethoxysilane, 3-methacrylamidopropylmethyldimethoxysilane, 3-methacrylamidopropyldimethylmethoxysilane, 3-Methacrylamidopropyltriethoxysilane, 3-Methacrylamidopropylmethyldiethoxysilane, 3-Methacrylamidopropyldimethylethoxysilane, 3-methacrylamidomethyltrimethoxysilane, 3-methacrylamidomethylmethyldimethoxysilane, 3-methacrylamidomethyldimethylmethoxysilane, 3-methacrylamidomethyltriethoxysilane, 3-methacrylamidomethylmethyldiethoxysilane, 3-methacrylamidomethyldimethylethoxysilane, 3-acrylamidopropyltrimethoxysilane, 3-acrylamidopropylmethyldimethoxysilane, 3-acrylamidopropyldimethylmethoxysilane, 3-acrylamidopropyltriethoxysilane, 3-acrylamidopropylmethyldiethoxysilane, 3-acrylamidopropyldimethylethoxysilane, 3-acrylamidomethyltrimethoxysilane, 3-acrylamidomethylmethyldimethoxysilane, 3-acrylamidomethyldimethylmethoxysilane, 3-Acrylamide methyl triethoxysilane, 3-Acrylamide methyl diethoxysilane, 3-Acrylamide methyl dimethyl ethoxysilane These include, but are not limited to, the following. Among these, from the viewpoints of availability and water solubility, the organosilicon compounds represented by the following formulae (1-1) to (1-4) are preferred, the organosilicon compound represented by the following formula (1-1) and the organosilicon compound represented by the following formula (1-3) are more preferred, and the organosilicon compound represented by the following formula (1-3) is particularly preferred, where Me represents a methyl group and Et represents an ethyl group.
[0017] [ka]
[0018] The component (A) may be a commercially available product, or may be produced by a known method. For example, the organosilicon compound represented by the above formula (1-1) and the organosilicon compound represented by the above formula (1-2) may be KBM-503 and KBE-503, both manufactured by Shin-Etsu Chemical Co., Ltd. The organosilicon compound represented by the above formula (1-3) and the organosilicon compound represented by the above formula (1-4) can be obtained, for example, according to the method described in Japanese Patent No. 3,561,501, by reacting methyl methacrylate with an aminoalkylalkoxysilane such as 3-aminopropyltrimethoxysilane in the presence of a polymerization inhibitor and an amidation catalyst at a temperature of about 100 to 200°C.
[0019] The component (A) may be used alone or in combination of two or more.
[0020] The concentration of component (A) in the glass cloth treatment liquid of the present invention is 0.05 to 2.0 mass%, preferably 0.1 to 1.0 mass%. If the concentration is less than 0.05 mass%, the amount of silane coupling agent relative to the silanol groups of the glass cloth is insufficient, and the strength of the glass cloth cannot be sufficiently improved. If the concentration is more than 2.0 mass%, the storage stability of the treatment liquid is impaired, and furthermore, the glass cloth becomes rigid, thereby reducing the productivity of the substrate material.
[0021] In the above formula (2), R 1 Examples of the alkyl group having 1 to 10 carbon atoms include the same as those exemplified above, and an alkyl group having 1 to 3 carbon atoms is preferred, a methyl group or an ethyl group is more preferred, and a methyl group is even more preferred.
[0022] m2 represents an integer of 1 to 3, with 2 or 3 being preferred.
[0023] R 3The monovalent aliphatic unsaturated hydrocarbon group having 4 to 12 carbon atoms may be linear, branched, or cyclic, but is preferably a linear or branched alkenyl group having 4 to 8 carbon atoms. Specific examples thereof include 1-butenyl, 2-butenyl, 3-butenyl, 1-methyl-2-propenyl, 2-methyl-1-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-methyl-3-butenyl, 2-methyl-3-butenyl, 3-methyl-3-butenyl, 1,1-dimethyl-2-propenyl, 1,2-dimethyl-2-propenyl, 3-methyl-2-butenyl, 2-methyl-2-butenyl, 1-ethyl-2-propenyl, propenyl, 2-ethyl-2-propenyl, 1-methyl-4-pentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, 5-hexenyl, 1-heptenyl, 2-heptenyl, 3-heptenyl, 4-heptenyl, 5-heptenyl, 6-heptenyl, 1-methyl-6-heptenyl, 1-octenyl, 2-octenyl, 3-octenyl, 4-octenyl, 5-octenyl, 6-octenyl, and 7-octenyl groups.
[0024] Specific examples of component (B) include: 3-butenyltrimethoxysilane, 3-butenylmethyldimethoxysilane, 3-butenyldimethylmethoxysilane, 3-butenyltriethoxysilane, 3-butenylmethyldiethoxysilane, 3-butenyldimethylethoxysilane, 2-butenyltrimethoxysilane, 2-butenylmethyldimethoxysilane, 2-butenyldimethylmethoxysilane, 2-butenyltriethoxysilane, 2-butenylmethyldiethoxysilane, 2-butenyldimethylethoxysilane, 1-butenyltrimethoxysilane, 1-butenylmethyldimethoxysilane, 1-butenyldimethylmethoxysilane, 1-butenyltriethoxysilane, 1-butenylmethyldiethoxysilane, 1-butenyldimethylethoxysilane, 1-methyl-2-propenyltrimethoxysilane, 1-methyl-2-propenylmethyldimethoxysilane, 1-methyl-2-propenyldimethylmethoxysilane, 1-methyl-2-propenyltriethoxysilane, 1-methyl-2-propenylmethyldiethoxysilane, 1-methyl-2-propenyldimethylethoxysilane, 2-Methyl-1-propenyltrimethoxysilane, 2-Methyl-1-propenylmethyldimethoxysilane, 2-Methyl-1-propenyldimethylmethoxysilane, 2-Methyl-1-propenyltriethoxysilane, 2-Methyl-1-propenylmethyldiethoxysilane, 2-Methyl-1-propenyldimethylethoxysilane, 4-pentenyltrimethoxysilane, 4-pentenylmethyldimethoxysilane, 4-pentenyldimethylmethoxysilane, 4-pentenyltriethoxysilane, 4-pentenylmethyldiethoxysilane, 4-pentenyldimethylethoxysilane, 3-pentenyltrimethoxysilane, 3-pentenylmethyldimethoxysilane, 3-pentenyldimethylmethoxysilane, 3-pentenyltriethoxysilane, 3-pentenylmethyldiethoxysilane, 3-pentenyldimethylethoxysilane, 2-pentenyltrimethoxysilane, 2-pentenylmethyldimethoxysilane, 2-pentenyldimethylmethoxysilane, 2-pentenyltriethoxysilane, 2-pentenylmethyldiethoxysilane, 2-pentenyldimethylethoxysilane, 1-pentenyltrimethoxysilane, 1-pentenylmethyldimethoxysilane, 1-pentenyldimethylmethoxysilane, 1-pentenyltriethoxysilane, 1-pentenylmethyldiethoxysilane, 1-pentenyldimethylethoxysilane, 1-methyl-3-butenyltrimethoxysilane, 2-methyl-3-butenyltrimethoxysilane, 3-methyl-3-butenyltrimethoxysilane, 1,1-dimethyl-2-propenyltrimethoxysilane, 1,2-dimethyl-2-propenyltrimethoxysilane, 3-methyl-2-butenyltrimethoxysilane, 2-methyl-2-butenyl-trimethoxysilane, 1-ethyl-2-propenyltrimethoxysilane, 2-ethyl-2-propenyltrimethoxysilane, 1-methyl-3-butenyltriethoxysilane, 2-methyl-3-butenyltriethoxysilane, 3-methyl-3-butenyltriethoxysilane, 1,1-dimethyl-2-propenyltriethoxysilane, 1,2-dimethyl-2-propenyltriethoxysilane, 3-methyl-2-butenyltriethoxysilane, 2-methyl-2-butenyl-triethoxysilane, 1-ethyl-2-propenyltriethoxysilane, 2-ethyl-2-propenyltriethoxysilane, 1-methyl-3-butenylmethyldimethoxysilane, 2-methyl-3-butenylmethyldimethoxysilane, 3-methyl-3-butenylmethyldimethoxysilane, 1,1-dimethyl-2-propenylmethyldimethoxysilane, 1,2-dimethyl-2-propenylmethyldimethoxysilane, 3-methyl-2-butenylmethyldimethoxysilane, 2-methyl-2-butenyl-methyldimethoxysilane, 1-ethyl-2-propenylmethyldimethoxysilane, 2-ethyl-2-propenylmethyldimethoxysilane, 1-methyl-4-pentenyltrimethoxysilane, 1-methyl-4-pentenylmethyldimethoxysilane, 1-methyl-4-pentenyldimethylmethoxysilane, 1-methyl-4-pentenyltriethoxysilane, 1-methyl-4-pentenylmethyldiethoxysilane, 1-methyl-4-pentenyldimethylethoxysilane, 5-hexenyltrimethoxysilane, 5-hexenylmethyldimethoxysilane, 5-hexenyldimethylmethoxysilane, 5-hexenyltriethoxysilane, 5-hexenylmethyldiethoxysilane, 5-hexenyldimethylethoxysilane, 4-hexenyltrimethoxysilane, 4-hexenylmethyldimethoxysilane, 4-hexenyldimethylmethoxysilane, 4-hexenyltriethoxysilane, 4-hexenylmethyldiethoxysilane, 4-hexenyldimethylethoxysilane, 3-Hexenyltrimethoxysilane, 3-Hexenylmethyldimethoxysilane, 3-Hexenyldimethylmethoxysilane, 3-Hexenyltriethoxysilane, 3-Hexenylmethyldiethoxysilane, 3-Hexenyldimethylethoxysilane, 2-hexenyltrimethoxysilane, 2-hexenylmethyldimethoxysilane, 2-hexenyldimethylmethoxysilane, 2-hexenyltriethoxysilane, 2-hexenylmethyldiethoxysilane, 2-hexenyldimethylethoxysilane, 1-hexenyltrimethoxysilane, 1-hexenylmethyldimethoxysilane, 1-hexenyldimethylmethoxysilane, 1-hexenyltriethoxysilane, 1-hexenylmethyldiethoxysilane, 1-hexenyldimethylethoxysilane, 6-heptenyltrimethoxysilane, 6-heptenylmethyldimethoxysilane, 6-heptenyldimethylmethoxysilane, 6-heptenyltriethoxysilane, 6-heptenylmethyldiethoxysilane, 6-heptenyldimethylethoxysilane, 1-methyl-6-heptenyltrimethoxysilane, 1-methyl-6-heptenylmethyldimethoxysilane, 1-methyl-6-heptenyldimethylmethoxysilane, 1-methyl-6-heptenyltriethoxysilane, 1-methyl-6-heptenylmethyldiethoxysilane, 1-methyl-6-heptenyldimethylethoxysilane, 5-heptenyltrimethoxysilane, 5-heptenylmethyldimethoxysilane, 5-heptenyldimethylmethoxysilane, 5-heptenyltriethoxysilane, 5-heptenylmethyldiethoxysilane, 5-heptenyldimethylethoxysilane, 4-heptenyltrimethoxysilane, 4-heptenylmethyldimethoxysilane, 4-heptenyldimethylmethoxysilane, 4-heptenyltriethoxysilane, 4-heptenylmethyldiethoxysilane, 4-heptenyldimethylethoxysilane, 3-heptenyltrimethoxysilane, 3-heptenylmethyldimethoxysilane, 3-heptenyldimethylmethoxysilane, 3-heptenyltriethoxysilane, 3-heptenylmethyldiethoxysilane, 3-heptenyldimethylethoxysilane, 2-heptenyltrimethoxysilane, 2-heptenylmethyldimethoxysilane, 2-heptenyldimethylmethoxysilane, 2-heptenyltriethoxysilane, 2-heptenylmethyldiethoxysilane, 2-heptenyldimethylethoxysilane, 1-heptenyltrimethoxysilane, 1-heptenylmethyldimethoxysilane, 1-heptenyldimethylmethoxysilane, 1-heptenyltriethoxysilane, 1-heptenylmethyldiethoxysilane, 1-heptenyldimethylethoxysilane, 7-octenyltrimethoxysilane, 7-octenylmethyldimethoxysilane, 7-octenyldimethylmethoxysilane, 7-octenyltriethoxysilane, 7-octenylmethyldiethoxysilane, 7-octenyldimethylethoxysilane, 6-octenyltrimethoxysilane, 6-octenylmethyldimethoxysilane, 6-octenyldimethylmethoxysilane, 6-octenyltriethoxysilane, 6-octenylmethyldiethoxysilane, 6-octenyldimethylethoxysilane, 5-octenyltrimethoxysilane, 5-octenylmethyldimethoxysilane, 5-octenyldimethylmethoxysilane, 5-octenyltriethoxysilane, 5-octenylmethyldiethoxysilane, 5-octenyldimethylethoxysilane, 4-octenyltrimethoxysilane, 4-octenylmethyldimethoxysilane, 4-octenyldimethylmethoxysilane, 4-octenyltriethoxysilane, 4-octenylmethyldiethoxysilane, 4-octenyldimethylethoxysilane, 3-octenyltrimethoxysilane, 3-octenylmethyldimethoxysilane, 3-octenyldimethylmethoxysilane, 3-octenyltriethoxysilane, 3-octenylmethyldiethoxysilane, 3-octenyldimethylethoxysilane, 2-octenyltrimethoxysilane, 2-octenylmethyldimethoxysilane, 2-octenyldimethylmethoxysilane, 2-octenyltriethoxysilane, 2-octenylmethyldiethoxysilane, 2-octenyldimethylethoxysilane, 1-Octenyltrimethoxysilane, 1-Octenylmethyldimethoxysilane, 1-Octenyldimethylmethoxysilane, 1-Octenyltriethoxysilane, 1-Octenylmethyldiethoxysilane, 1-Octenyldimethylethoxysilane These include, but are not limited to, the following.
[0025] Among these, from the viewpoints of availability and water solubility, the organosilicon compounds represented by the following formulae (2-1) to (2-11) are preferred, and the organosilicon compounds represented by the following formulae (2-3) to (2-10) are particularly preferred, where Me represents a methyl group.
[0026] [ka]
[0027] The (B) component may be a commercially available product, or may be produced by a known method. For example, the organosilicon compound represented by the above formula (2-10) and the organosilicon compound represented by the above formula (2-11) may be KBM-1063 and KBM-1083, both manufactured by Shin-Etsu Chemical Co., Ltd. In addition, the organosilicon compounds represented by the above formulas (2-3) to (2-9) can be obtained, for example, by reacting one of the carbon-carbon double bonds of isoprene with a hydrogen atom (Si-H group) bonded to a silicon atom of a hydrosilane such as trimethoxyhydrosilane in the presence of a metal catalyst (hydrosilylation).
[0028] The ratio of isoprene to hydrosilane used in the reaction is not particularly limited, but is preferably 0.4 mol or more and less than 1.5 mol, and more preferably 0.6 mol or more and less than 1.2 mol, of hydrosilane per 1 mol of the isoprene compound.
[0029] The metal catalyst used in the above reaction is not particularly limited. From the viewpoints of availability and reactivity, a platinum compound-containing catalyst or a rhodium compound catalyst is preferred, and a rhodium compound catalyst is more preferred. For example, chlorotris(triphenylphosphine)rhodium(I) and the like are suitable. The reaction temperature is not particularly limited, and the reaction can be carried out from 0° C. under heating, preferably 40 to 110° C., and the reaction time is usually about 1 to 20 hours.
[0030] The component (B) may be used alone or in combination of two or more. When two or more types are combined, a mixture of the compounds represented by the above formulas (2-3) to (2-9) is preferred.
[0031] The concentration of the (B) component in the glass cloth treatment liquid of the present invention is 0.05 to 2.0 mass%, preferably 0.1 to 1.0 mass%. If the concentration is less than 0.05 mass%, the amount of the silane coupling agent relative to the silanol groups of the glass cloth is insufficient, and the strength of the glass cloth cannot be sufficiently improved. If the concentration exceeds 2.0 mass%, the storage stability of the treatment liquid is impaired, and furthermore, the glass cloth becomes rigid, thereby reducing the productivity of the substrate material.
[0032] The total concentration of the components (A) and (B) in the glass cloth treatment liquid of the present invention is preferably from 0.1 to 2.5% by mass, more preferably from 0.2 to 2.0% by mass. The content ratio of the component (A) and the component (B) in the glass cloth treatment liquid of the present invention is preferably 1:10 to 10:1 in terms of mass ratio.
[0033] The glass cloth treatment liquid of the present invention can be prepared by mixing the components (A), (B) and water and dissolving the components (A) and (B) in the water. In this case, the components (A) and (B) may be added to the water, or the water may be added to a mixture of the components (A) and (B), but a method in which the components (A) and (B) are mixed while being dropped into the water is preferred. The temperature during mixing is preferably from 10 to 50°C, more preferably from 15 to 40°C.
[0034] The glass cloth treatment liquid of the present invention may contain, in addition to the components (A) and (B) and water, an organic solvent within a range that does not impair the effects of the present invention. The organic solvent is not particularly limited, but is preferably an organic solvent having excellent compatibility with water. Examples of the organic solvent include alcohols such as methanol, ethanol, and isopropanol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; esters such as ethyl acetate; and ketones such as acetone and methyl ethyl ketone. One type of organic solvent may be used alone, or two or more types may be used in combination. When an organic solvent is used, its blending amount is not particularly limited, but is preferably 5 to 50% by mass, and more preferably 10 to 30% by mass, of the entire treatment liquid.
[0035] From the viewpoint of stability, the glass cloth treatment liquid of the present invention preferably uses water adjusted to be acidic. Examples of acids for adjusting the acidity include organic acids such as formic acid, acetic acid, and citric acid, and inorganic acids such as hydrochloric acid. When an acid is used, the amount of the acid added is preferably 0.001 to 0.5 mass % of the total treatment liquid, and more preferably 0.01 to 0.1 mass %. When an acid is used, water that has been adjusted to be acidic in advance by mixing the acid with water may be used, or the acid may be added to an aqueous solution containing the (A) component and the (B) component to adjust the acidity.
[0036] To the glass cloth treatment liquid of the present invention, if necessary, an alkoxy group-containing organosilicon compound, a silazane compound, etc. other than components (A) and (B) can be added in order to improve the adhesion and bonding properties with the glass cloth, provided that the effect of the present invention is not impaired. In addition, other additives may be added to the glass cloth treatment liquid of the present invention as necessary within the scope of not impairing the effects of the present invention. Specific examples of other additives include water-soluble resins, curing catalysts, physical property adjusters for adjusting the tensile properties of the resulting cured coating, storage stability improvers, surfactants, metal deactivators, antiozonants, lubricants, pigments, etc.
[0037] [Surface-treated glass cloth] The surface-treated glass cloth of the present invention is a glass cloth whose surface has been treated with the above-mentioned treatment liquid. The surface-treated glass cloth of the present invention can be obtained by applying the glass cloth treatment liquid of the present invention to the surface of a glass cloth, and optionally drying it by heating.
[0038] [1] Glass cloth The glass yarn constituting the glass cloth used as the substrate is not particularly limited, and glass compositions having a conventionally known glass composition can be used. Specific examples thereof include E glass, S glass, C glass, D glass, T glass, NE glass, and Q glass (quartz glass), and are appropriately selected depending on the intended use. The form of the glass yarn is not particularly limited, and examples thereof include a filament, a strand obtained by bundling 20 to 400 filaments, and a yarn obtained by twisting a strand.
[0039] The thickness of the glass cloth is not particularly limited, but is preferably 5 to 300 μm, more preferably 20 to 200 μm, and even more preferably 30 to 150 μm. The mass per unit area is not particularly limited, but is preferably 10 to 200 g / m 2 is preferable, and 20 to 150 g / m 2 is preferred. The weave of the glass cloth is not particularly limited, and examples thereof include plain weave, twill weave, twill weave, satin weave, etc., which are appropriately selected depending on the application, and the weave density is also appropriately selected within the conventionally known range.
[0040] [2] Manufacturing method of glass cloth The method for producing the glass cloth used as the substrate is not particularly limited as long as it includes a step of weaving glass yarn. For example, a method including the following steps may be mentioned. (1) Weaving process to obtain glass cloth by weaving glass yarn (2) Spreading process to spread the glass threads of the glass cloth (3) A heat cleaning process to remove sizing agents from the glass threads of glass cloth
[0041] (1) Weaving process The weaving process is a process in which glass yarn is woven to obtain glass cloth. The weaving method is not particularly limited, but examples thereof include weaving methods using an air jet loom, a water jet loom, a rapier loom, a shuttle loom, etc. When weaving is performed using an air jet loom, etc., PVA or starch can be attached as a secondary sizing agent to obtain further lubricity.
[0042] (2) Opening process The opening process is a process for opening the glass yarns of the glass cloth. The opening method is not particularly limited, but examples thereof include opening processing methods using spray water (high pressure water opening), a vibro washer, ultrasonic water, a mangle, etc.
[0043] (3) Heat cleaning process The heat cleaning process is a process for removing the sizing agent remaining on the surface of the glass cloth after weaving. When the surface-treated glass cloth is used as a substrate material, the remaining sizing agent undesirably deteriorates the dielectric properties and also causes insufficient surface treatment of the glass cloth, resulting in poor adhesion with the resin. Heat cleaning methods include methods using flow and batch heating furnaces. The flow method burns off the sizing agent all at once at high temperature, which can cause problems such as a decrease in the strength of the glass cloth and residual sizing agent, so the batch method is generally used, which burns off the organic matter gradually at 300 to 400°C.
[0044] [3] Surface treatment method for glass cloth The method for treating the surface of a glass cloth with the glass cloth treatment liquid of the present invention is not particularly limited, but can be carried out, for example, by a method including the following steps. (11) A treatment liquid contacting step of contacting the surface of a glass cloth with the glass cloth treatment liquid of the present invention. (12) A reaction step in which silanol groups on the surface of the glass cloth are reacted with alkoxy groups or silanol groups in the components (A) and (B) contained in the glass cloth treatment liquid of the present invention.
[0045] (11) Treatment liquid contact step The treatment liquid contact step is a step of contacting the glass cloth surface with the glass cloth treatment liquid of the present invention. In the treatment liquid contact step, the contact method is not particularly limited and may be appropriately selected from known methods, for example, a method of permeating the glass cloth with the glass cloth treatment liquid of the present invention, a method by roll coating, etc.
[0046] (12) Reaction process The reaction step is a step of reacting the silanol groups on the glass cloth surface with the alkoxy groups or silanol groups in the components (A) and (B) contained in the glass cloth treatment liquid of the present invention. In the reaction step, the reaction conditions are not particularly limited and may be appropriately adjusted depending on the heat resistance of the glass yarn, the amount of the glass cloth treatment liquid used, etc., but the reaction temperature is preferably 70 to 200°C, more preferably 90 to 150°C. The reaction time is preferably 30 seconds to 30 minutes, more preferably 1 to 20 minutes. Under such conditions, water can be evaporated and the alkoxy groups or silanol groups in the components (A) and (B) can react with the silanol groups on the glass cloth surface. The heating method is not particularly limited and may be appropriately selected from known methods, for example, methods using hot air, infrared rays, hot rolls, etc.
[0047] In the surface-treated glass cloth of the present invention, the adhesion amount of the components (A) and (B) to the glass cloth substrate is not particularly limited, but from the viewpoints of processability and strength, the adhesion amount is preferably 0.05 to 0.5 mass%, more preferably 0.05 to 0.2 mass% in total. The adhesion amount of the components (A) and (B) can be measured by the ignition loss according to JIS R3420:2013.
[0048] The surface-treated glass cloth of the present invention has a cloth mass (g / mm 2 The tensile strength per unit area is preferably 2.1 times or more, and more preferably 2.2 times or more, compared to that before the surface treatment. Such a surface-treated glass cloth has excellent processability when made into a prepreg. As will be described later, the tensile strength can be measured in accordance with "7.4 Tensile strength" of JIS R3420:2013 "General test methods for glass fibers."
[0049] [Prepreg] The prepreg of the present invention contains the above-mentioned surface-treated glass cloth and a matrix resin impregnated into the surface-treated glass cloth. The surface-treated glass cloth of the present invention can be mixed with a matrix resin to form a prepreg. The prepreg obtained by using the surface-treated glass cloth of the present invention has excellent strength and can be suitably used for, for example, printed wiring boards.
[0050] The method for producing the prepreg of the present invention is not particularly limited, and general methods for producing glass cloth-containing substrates, films, prepregs, etc. can be applied. For example, a method in which a molten matrix resin or a solution containing a matrix resin is impregnated into a surface-treated glass cloth can be used. The matrix resin used in the prepreg of the present invention is not particularly limited and can be appropriately selected from conventionally known ones, for example, thermosetting silicone resin, polyimide resin, maleimide resin, epoxy resin, cyanate resin, (meth)acrylic resin, polyphenylene ether resin, etc. These may be used alone or in combination of two or more. Among these, polyphenylene ether resin is preferred.
[0051] The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 400 μm, more preferably 30 to 300 μm, and even more preferably 40 to 200 μm. Within this range, for example, when the prepreg of the present invention is used for a printed wiring board, a board such as a copper-clad laminate can be well prepared. The prepreg of the present invention may be semi-cured (B-staged) in advance by heating. There are no particular limitations on the method for B-staging, but for example, the matrix resin may be dissolved in a solvent, impregnated into glass cloth, dried, and then heated at a temperature of 80 to 200°C for 1 to 30 minutes to achieve B-stage.
[0052] [Printed wiring board] The printed wiring board of the present invention is obtained by using a prepreg containing the surface-treated glass cloth of the present invention. The method for producing the printed wiring board of the present invention is not particularly limited, and a general method for producing a printed wiring board can be applied. A specific example is a method in which the prepreg of the present invention and a copper foil are stacked and pressed, and then heat-cured to produce a substrate as a copper-clad laminate. The method for producing a copper-clad laminate is not particularly limited, and for example, the copper-clad laminate can be produced by using 1 to 20 sheets, preferably 2 to 10 sheets, of the above prepreg, arranging copper foil on one or both sides of the prepreg, pressing, and heat-curing.
[0053] The thickness of the copper foil is not particularly limited, but is preferably 3 to 70 μm, more preferably 10 to 50 μm, and even more preferably 15 to 40 μm. Within this range, a multi-layer copper-clad laminate with high reliability can be formed. The molding conditions for the copper-clad laminate are not particularly limited, but for example, it can be molded using a multi-stage press, a multi-stage vacuum press, a continuous molding machine, an autoclave molding machine, or the like, at a temperature of 100 to 400° C., a pressure of 1 to 100 MPa, and a heating time of 0.1 to 4 hours. In addition, the prepreg of the present invention, the copper foil, and the wiring board for the inner layer can be combined and molded to form a copper-clad laminate.
[0054] The method of circuit processing is not particularly limited, and examples thereof include circuit formation processing methods such as drilling, metal plating, etching of metal foil, etc. In addition, a printed wiring board may be produced by a build-up method in which a composition containing a matrix resin or the prepreg of the present invention and copper foil are sequentially laminated. EXAMPLES
[0055] The present invention will be described in more detail below with reference to Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited to these Examples. In the following formulae, Me represents a methyl group, and Et represents an ethyl group.
[0056] [1] Synthesis of organosilicon compounds [Synthesis Example 1] With reference to Japanese Patent No. 3561501, an organosilicon compound (1-3) represented by the following formula was obtained.
[0057] [ka]
[0058] [Synthesis Example 2] In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 0.55g of chlorotris(triphenylphosphine)rhodium(I), 300.0g of toluene, 0.3g of 2,6-di-t-butyl-p-cresol and 0.1g of tetrabutylammonium bromide were placed, and 125.4g (1.84 mol) of isoprene and 150.0g (1.23 mol) of trimethoxyhydrosilane were added dropwise at an internal temperature of 60-70°C over 2 hours. The mixture was then stirred at 60°C for 5 hours, and analyzed by gas chromatography, confirming the disappearance of trimethoxyhydrosilane. The resulting solution was purified by distillation at 20mmHg and 80°C to obtain a kinetic viscosity of 1.2mm. 2 / s, and a refractive index of 1.420. 1 By 1 H-NMR measurement and gas chromatography mass spectrometry (GC / MS) measurement, it was confirmed that the obtained product was a mixture (2) of compounds represented by the following formulas (2-3) to (2-9).
[0059] [ka]
[0060] In the above examples, the kinematic viscosity and refractive index were measured at 25°C. In this case, the kinematic viscosity was measured based on JIS Z 8803. The refractive index was measured in accordance with JIS K 0062. Nuclear magnetic resonance spectrum ( 1 H-NMR measurements were performed in deuterated chloroform using an AVANCE III / ULTRASIELD 400 manufactured by BRUKER. Gas chromatography mass spectrometry (GC / MS) measurements were performed under the following conditions. GC equipment: Agilent Technologies 7200 Q-TOF GC / MS Detector: FID & TTOF-MS Column: HP-5 S-433 (length 30 m x inner diameter 0.25 mm, film thickness 0.25 μm) Column temperature: 50°C → 10°C / min → 280°C (10 min hold) Inlet temperature: 250℃ Detector temperature: 300℃ Carrier gas: He Carrier gas flow rate: 30mL / min Ionization method: EI Ion source temperature: 250℃ Mass range: m / z=30-1000
[0061] [2] Manufacturing of glass cloth treatment liquid [Examples 1-1 to 1-12, Comparative Examples 1-1 to 1-5] According to the blending ratios shown in Tables 1 and 2, the following components (A) and (B) were added dropwise to and mixed with 0.05% by mass acetic acid in water at 25°C to produce glass cloth treatment solutions i to xvii. In Examples 1 to 12, a mixed solvent of 0.05% by mass acetic acid in water and methanol was used. The obtained glass cloth treatment solutions were evaluated as follows. The results are shown in Tables 1 and 2.
[0062] [Stability of Glass Cloth Treatment Solution] The obtained glass cloth treatment liquid was allowed to stand in an environment of 25° C. for 1 day and 3 days, after which the appearance was visually observed and evaluated according to the following criteria. ◯: Completely dissolved, forming a homogeneous aqueous solution. ×: Insoluble matter precipitated.
[0063] [Table 1]
[0064] [Table 2]
[0065] Each component shown in Tables 1 and 2 will be explained below. Component (A) KBM-503: 3-(methacryloyloxy)propyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.) KBM-502: 3-(methacryloyloxy)propylmethyldimethoxysilane (Shin-Etsu Chemical Co., Ltd.) KBE-503: 3-(methacryloyloxy)propyltriethoxysilane (Shin-Etsu Chemical Co., Ltd.) Compound (1-3): Organosilicon compound obtained in Synthesis Example 1 (B) Component Mixture (2): Mixture of organosilicon compounds obtained in Synthesis Example 2 KBM-1063: 5-Hexenyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.) KBM-1083: 7-Octenyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.)
[0066] [3] Manufacturing of surface-treated glass cloth [Examples 2-1 to 2-12, Comparative Examples 2-1 to 2-5] The E-glass cloth (thickness: 95 μm, mass per unit area: 107 g / m) obtained by heating at 400 °C for 72 hours to remove the sizing agent was 2 ) was immersed in the glass cloth treatment solutions obtained in Examples 1-1 to 1-12 and Comparative Examples 1-1, 1-2 and 1-5, taken out, and then heated and dried at 110° C. for 10 minutes to obtain surface-treated glass cloths. In Comparative Examples 2-2 and 2-3, the stability of the glass cloth treatment liquid was low, and the surface treatment of the glass cloth could not be performed.
[0067] [4] Manufacturing of prepregs and cured prepregs The surface-treated glass cloth was impregnated with a matrix resin (M-1), and the solvent was removed by heating and drying at 100°C for 10 minutes to obtain a prepreg. Next, five prepregs were stacked and heat-cured at 180°C for 90 minutes under a pressure of 2.5 MPa using a vacuum press to produce a cured prepreg. Here, the matrix resin (M-1) is a mixture of 60 parts by mass of reactive low molecular weight polyphenylene ether (product name: SA-9000, manufactured by SABIC), 25 parts by mass of liquid styrene butadiene rubber (product name: RICON100, manufactured by Cray Valley), 15 parts by mass of triallyl isocyanurate, and 55 parts by mass of toluene (resin concentration: 64.5% by mass), to which 2 parts of dicumyl peroxide were added as a curing catalyst.
[0068] The obtained cured prepregs were subjected to the following evaluations, and the results are shown in Tables 3 and 4. [Solder heat resistance test] The obtained cured prepreg was cut into a 5 cm square, boiled in ion-exchanged water for 2 hours, and then immersed in a solder bath at 260°C for 30 seconds. The appearance of the cured product was observed and evaluated according to the following criteria. ○: No swelling occurs. ×: Swelling occurred. [Alkaline immersion test] The obtained cured prepreg was cut into a 5 cm square, the cut cured product was immersed in a 1N aqueous sodium hydroxide solution for 24 hours, and the appearance of the cured product was observed and evaluated according to the following criteria. ◯: No whitening or slight whitening at the edge. △: Bleaching extended to near the center. ×: The entire surface was whitened.
[0069] [Table 3]
[0070] [Table 4]
[0071] As shown in Table 1, the glass cloth treatment solutions i to xii obtained in Examples 1-1 to 1-12 had excellent storage stability, and as shown in Table 3, the prepreg cured products produced using glass cloth surface-treated with the glass cloth treatment solutions i to xii exhibited excellent solder heat resistance and alkali resistance. On the other hand, as shown in Table 4, the prepreg cured products produced using the glass cloth surface-treated with the glass cloth treatment liquids obtained in Comparative Examples 1-1 and 1-2 were poor in alkali resistance, and the glass cloth treatment liquids obtained in Comparative Examples 1-3 and 1-4 were poor in stability, making it difficult to surface treat the glass cloth. Furthermore, the prepreg cured product produced using the glass cloth surface-treated with the glass cloth treatment liquid obtained in Comparative Example 1-5 was significantly inferior in solder heat resistance and alkali resistance.
Claims
1. A glass cloth treatment liquid comprising (A) an organosilicon compound represented by the following formula (1) and (B) an organosilicon compound represented by the following formula (2) dissolved in a solvent containing water, A glass cloth treatment liquid having a concentration of component (A) of 0.05 to 2.0 mass % and a concentration of component (B) of 0.05 to 2.0 mass %. 【Chemistry 1】 (In the formula, R 1 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 represents a hydrogen atom or a methyl group, Me represents a methyl group, X represents an oxygen atom or NH, R 3 represents a monovalent aliphatic unsaturated hydrocarbon group having 4 to 12 carbon atoms, m1 and m2 each independently represent an integer of 1 to 3, and n1 represents an integer of 1 to 12.
2. In the above formula (1), R 2 2. The glass cloth treatment liquid according to claim 1, wherein n is a methyl group and n1 is 3.
3. In the above formula (2), R 3 2. The glass cloth treatment liquid according to claim 1, wherein is a linear or branched alkenyl group having 4 to 8 carbon atoms.
4. The glass cloth treatment liquid according to any one of claims 1 to 3, wherein the water is adjusted to be acidic.
5. 5. A surface-treated glass cloth, the surface of which has been treated with the glass cloth treatment liquid according to claim 4.
6. A prepreg comprising the surface-treated glass cloth according to claim 5 and a matrix resin impregnated into the surface-treated glass cloth.
7. A printed wiring board using the prepreg according to claim 6.
Citation Information
Patent Citations
Glass cloth, prepreg, and printed wiring board
JP7015972B1
Surface-treated glass cloth, prepreg, and printed wiring board
WO2020194772A1